Longitudinal Outcome over Two Decades of Unrelated Allogeneic Stem Cell Transplantation for Relapsed/ Refractory Acute Myeloid Leukemia: An ALWP/EBMT Analysis - Nagler, Arnon; Ngoya, Maud; Galimard, Jacques-Emmanuel; Labopin, Myriam; Bornhaeuser, Martin; Stelljes, Matthias; Finke, Juergen; Ganser, Arnold; Einsele, Herman; Kroeger, Nicolaus; Brecht, Arne; Bethge, Wolfgang; et al. (Clinical Cancer Research, 2022)
Purpose: We evaluated outcomes of unrelated transplantation for primary refractory/relapsed (ref/rel) acute myeloid leukemia (AML), comparing two cohorts according to the year of transplant, 2000-2009 and 2010-2019. Patients and Methods: Multivariable analyses were performed using the Cox proportional-hazards regression model. Results: 3,430 patients were included; 876 underwent a transplant between 2000-2009 and 2554 in 2010-2019. Median followup was 8.7 (95% CI, 7.8-9.4) and 3.4 (95% CI, 3.1-3.6) years (P < 0.001). Median age was 52 (18-77) and 56 (18-79) years (P > 0.0001); 45.5% and 55.5% had refractory AML while 54.5% and 44.5% had relapsed AML. Conditioning was myeloablative in 60% and 52%, respectively. Neutrophil recovery and day 100 incidence of acute and 2-year incidence of chronic graft-versus-host disease (GvHD) were similar between the two periods. Two-year relapse incidence was higher for patients undergoing transplant in the 2000-2009 period versus those undergoing transplant in 2010- 2019: 50.2% versus 45.1% (HR, 0.85; 95% CI, 0.74-0.97; P=0. 002). Leukemia-free survival; overall survival; and GvHD-free, relapsefree survival were lower for the 2000-2009 period: 26% versus 32.1% (HR, 0.87; 95% CI, 0.78-0.97; P = 0.01), 32.1% versus 38.1% (HR, 0.86; 95% CI, 0.77-0.96; P = 0.01), and 21.5% versus 25.3% (HR, 0.89; 95% CI, 0.81-0.99; P = 0.03), respectively. Two-year nonrelapse mortality was not significantly different (23.8% vs. 23.7%; HR, 0.91; 95% CI, 0.76-1.11; P = 0.34). Conclusions: Outcome of unrelated transplantation for patients with ref/rel AML has improved in the last two decades, rescuing about one third of the patients.
CRIS-Team Scopus Importer:2023-03-23